Legal and illegal cartels in Germany between 1958 and 2004 - Justus Haucap; Ulrich Heimeshoff; Luis Manuel Schultz (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
This paper offers a new and broad insight into the landscape of German cartels, utilizing a unique dataset of all illegal horizontal cartels detected by the German Federal Cartel Office (FCO) between 1958 and 2004 and all legal cartels authorized during the same time period. We also provide the first comparison of legal and illegal cartels in Germany. Legal cartels tend to last longer and to have more members than illegal cartels, while there are little differences with respect to the industries involved. The construction industries are the most cartelized sectors in Germany (29.8% of all legal cartels, 43.2% of all illegal cartels) followed by manufacture of metals and machinery (21.9% of all legal cartels, 30.6% of all illegal cartels). How the number of cartel members affects the duration of cartels is ambiguous. Cartels with no more than 12 members tend to last longer than cartels with more than 12 members. However, cartels with 5 to 12 members also tend to last longer than cartels with less than 5 members.
Keywords: 330; Horizontale Konzentration; Wettbewerbsrecht; Wettbewerbsaufsicht; Organisationsforschung; Kartell; Deutschland